2000
DOI: 10.1086/302749
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosomes Traveling South: The Cohen Modal Haplotype and the Origins of the Lemba—the “Black Jews of Southern Africa”

Abstract: The Lemba are a traditionally endogamous group speaking a variety of Bantu languages who live in a number of locations in southern Africa. They claim descent from Jews who came to Africa from "Sena." "Sena" is variously identified by them as Sanaa in Yemen, Judea, Egypt, or Ethiopia. A previous study using Y-chromosome markers suggested both a Bantu and a Semitic contribution to the Lemba gene pool, a suggestion that is not inconsistent with Lemba oral tradition. To provide a more detailed picture of the Lemba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
127
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 16 publications
8
127
1
Order By: Relevance
“…15,65 The Lemba have high frequencies of the Middle Eastern Y-chromosome HgJ-12f2a (25%), a potentially SEA Y, Hg-K(xPQR) (32%) and a Bantu Y, E-PN1 (30%) (similar to E-M2), raising the possibility that the Lemba and Comorian populations are consequences of similar demographic processes. The high-resolution genotyping of the Lemba Y chromosomes and mitochondria will elucidate this question.…”
Section: Discussionmentioning
confidence: 99%
“…15,65 The Lemba have high frequencies of the Middle Eastern Y-chromosome HgJ-12f2a (25%), a potentially SEA Y, Hg-K(xPQR) (32%) and a Bantu Y, E-PN1 (30%) (similar to E-M2), raising the possibility that the Lemba and Comorian populations are consequences of similar demographic processes. The high-resolution genotyping of the Lemba Y chromosomes and mitochondria will elucidate this question.…”
Section: Discussionmentioning
confidence: 99%
“…The Lemba, as discussed earlier, provide a more recent example. In this case, Y-DNA provides evidence for extensive interbreeding between Jewish and Bantu populations, but mtDNA indicates that there was no interbreeding at all, a pattern consistent with their oral history (Soodyall, 1993;Thomas et al, 2000;Wilson and Goldstein, 2000). Thus, mtDNA alone is biologically incapable of detecting all admixture events, even those such as the Lemba in which the degree of admixture was 100% (given that their origin was due to Jewish men mating with Bantu women).…”
Section: Haplotype Trees With Ancient Dnamentioning
confidence: 94%
“…For example, Thomas et al (2000) identified several Y-chromosomal haplotypes from the tips of the Y-DNA haplotype tree that were also of restricted geographical distribution. They surveyed Y-chromosomal variation in the Lemba, a southern African group who speak a variety of Bantu languages but claim Jewish ancestry .…”
Section: Tracing Recent Haplotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Mitochondrial DNA analyses have been performed on collections from Qatar, United Arab Emirates (UAE) and Yemen, 5,20 yet the paternal component of this historically and geographically significant region is incomplete. Although Y-chromosome studies have focused on neighboring areas, including Egypt, 4 Somalia, 21 Iraq, 22 Syria and Lebanon 23 as well as on the southern Arabian populations of Oman 4 and Yemen, 24 high resolution Y-chromosome analyses of the Persian and Oman Gulfs are fragmentary.…”
Section: Introductionmentioning
confidence: 99%